Deficiency in Galectin-3 Promotes Hepatic Injury in CDAA Diet-Induced Nonalcoholic Fatty Liver Disease. (19th April 2012) - Nomoto, Kazuhiro; Nishida, Takeshi; Nakanishi, Yuko; Fujimoto, Makoto; Takasaki, Ichiro; Tabuchi, Yoshiaki; Tsuneyama, Koichi
Abstract : Nonalcoholic fatty liver disease (NAFLD) is increasingly recognized as a condition in which excess fat accumulates in hepatocytes. Nonalcoholic steatohepatitis (NASH), a severe form of NAFLD in which inflammation and fibrosis in the liver are noted, may eventually progress to end-stage liver disease. Galectin-3, a β-galactoside-binding animal lectin, is a multifunctional protein. This protein is involved in inflammatory responses and carcinogenesis. We investigated whether galectin-3 is involved in the development of NASH by comparing galectin-3 knockout (gal3 − / − ) mice and wild-type (gal3 + / + ) mice with choline-deficient L-amino-acid-defined (CDAA) diet-induced NAFLD/NASH. Hepatic injury was significantly more severe in the gal 3 − / − male mice, as compared to the gal 3 + / + mice. Data generated by microarray analysis of gene expression suggested that galectin-3 deficiency causes alterations in the expression of various genes associated with carcinogenesis and lipid metabolism. Through canonical pathway analysis, involvement of PDGF and IL-6 signaling pathways was suggested in galectin-3 deficiency. Significant increase of CD14, Fos, and Jun, those that were related to lipopolysaccharide-mediated signaling, was candidate to promote hepatocellular damages in galectin-3 deficiency. In conclusion, galectin-3 deficiency in CDAA diet promotes NAFLD features. It may be caused by alterations in the expression profiles of various hepatic genes including lipopolysaccharide-mediated inflammation.